1990
DOI: 10.1580/0953-9859-1.4.235
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of mountaineering and rock climbing accidents

Abstract: From 1981 through 1986, 43631 climbers registered for climbs in the Grand Teton National Park, USA. There were 108 climbing accidents. The accident incidence was 2.5 accidents per 1000 climbers per year, or 5.6 accidents per 10000 climber-hours. There were 23 fatal accidents and 25 fatalities. Mountaineering appears to be a more hazardous activity than rock climbing; travel over snow or ice-covered terrain accounted for high numbers of accidents, climber errors, and fatalities. Effective use of proper equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 5 publications
1
66
0
1
Order By: Relevance
“…In fatal accidents, significantly more men are involved than women (p < 0.05) [30]. Schussmann et al [32] reported an incidence of 2.5 accidents/1,000 mountaineers and year or 0.56/1,000 h of mountaineering. Most studies on mountaineering fatalities and accidents present the injury/fatality number per 1,000 climbers or per 1,000 32] reported that most climbing injuries involved the lower extremities and resulted from big swings into the wall or big falls [4,23].…”
Section: Mountaineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…In fatal accidents, significantly more men are involved than women (p < 0.05) [30]. Schussmann et al [32] reported an incidence of 2.5 accidents/1,000 mountaineers and year or 0.56/1,000 h of mountaineering. Most studies on mountaineering fatalities and accidents present the injury/fatality number per 1,000 climbers or per 1,000 32] reported that most climbing injuries involved the lower extremities and resulted from big swings into the wall or big falls [4,23].…”
Section: Mountaineeringmentioning
confidence: 99%
“…Schussmann et al [32] reported an incidence of 2.5 accidents/1,000 mountaineers and year or 0.56/1,000 h of mountaineering. Most studies on mountaineering fatalities and accidents present the injury/fatality number per 1,000 climbers or per 1,000 32] reported that most climbing injuries involved the lower extremities and resulted from big swings into the wall or big falls [4,23]. The authors suggest that these findings may be partially explained by the minor nature of many rock climbing-related injuries recalled by participants in the other surveys.…”
Section: Mountaineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most research indicates that the upper extremity to be the most injured body region in non-alpine rock-climbing [2,3,5,6,10,14,15,40,60,[64][65][66][67][68][69][70][71][72] . Schöffl et al [61] analysed 604 injured climbers (sport climbing, indoor climbing) and reported 247 of 604 (40.9%) injuries involved the hand, 9.1% the foot.…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 99%
“…In the past 20 years several studies (pro-and retrospectively) were conducted to evaluate the injury and fatality risk of rock [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] , ice 19,20 and mountain climbing [16][17][18][21][22][23][24][25][26][27][28][29][30] . Injury incidence was reported per 1000 hours of sport-specific performance, expedition days, summit attempts or other.…”
Section: Introductionmentioning
confidence: 99%